DAMPAK OFFICE CHANNELLING TERHADAP KENAIKAN THIRD PARTY DEPOSITS DAN RETURN ON ASSETS UNIT USAHA SYARI'AH - Tenny Badina; Ina Indriana; Yeni Januarsi (Media Riset Bisnis & Manajemen, 2009)
The objectives of the research is to study and to analyze empirically the influence of office channelling on third party deposits and return on assets in Indonesian sharia business unit. Third party deposits and return on assets are used as indicators of sharia business unit performance after opening new branchs through office channelling program. The research uses korelasional method.The number of sharia business units taken as samples in the research cover about 10 sharia business unit in Indonesia which already publicate theirs own financial statements separated from their conventional banks financial statements. The data were analyzed using Ordinary Least Square Method.The result show that, firstly, office channelling statistically significant influence third party deposits, but secondly, office channelling statistically insignificant influence return on assets. This unpredicted result shows that the increase of third party deposits through office channelling program not automatically could increase return on assets. We found that the sharia business unit couldn't yet opfimally response the increase of third party deposits. The increasing of third party deposits were not followed yet by the good atocafions of fund.Keywords : Office channelling, Third party deposits, Return on assets, Sharia business unit, Performance